The operational process efficiency and profitability on food and beverage companies in Indonesia - Pratiwi, Melda Febi Jeri; Yuniarti, Sari; Sunardi, Sunardi; Prihantono, Eko Yuni (Jurnal Penelitian, 2023)
High profitability can create attractiveness for investors, and also provide opportunities for company growth. Improving profitability can be achieved through efforts to enhance operational efficiency and optimize the allocation of company resources. This research aims to investigate the impact of Receivable Turnover (RTO) and Inventory Turnover (ITR) on Profitability (ROA) in the food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2018-2022. Data collection methods involve documentation, utilizing financial reports from six companies with the highest sales turnover. Using multiple linear regression analysis, the research findings reveal that Receivable Turnover (RTO) significantly influences Profitability (ROA) positively. This indicates that increased efficiency in receivables management can contribute positively to a company’s profitability. Meanwhile, Inventory Turnover (ITR) does not have a significant impact on ROA. This finding suggests that efficiency in inventory management does not directly affect the level of profitability. The implications of this research underscore the importance for management to maintain efficiency in receivables management and continually improve operational efficiency in inventory management. Thus, companies can more quickly convert inventory into sales, avoid excess idle inventory, and overall improve profitability performance.